Konstruksi Pemberitaan Terorisme Surabaya di Media Onlie Detik dan Kompas - Putra, Yulian Dwi (Institut Agama Islam Negeri (IAIN) Curup, 2018)
Terror in the information society today has become part of the world of information itself. That is, there is terror in the form of information, there is information about terror, and there is terror that uses information media as a way of communication. This is an advantage for terrorists in carrying out their acts of terror because every action is informed by various media. This study aims to see how online media framing Detik.Com and Kompas.Com in reporting terrorism in Surabaya. This research is a qualitative study with a framing analysis approach of the Pan Kosicki model. This research paradigm uses the constructivism paradigm (constructivism paradigm). The object in this study is the reporting of online media Detik.Com and Kompas.Com which deals with terrorism in Surabaya, especially in May 2018. From the results of framing both online media, it can be seen that the news published significantly has not been interpreted specifically to construct messages from news of these two online media on the effects. The reporting conducted by both online media as well as the results of data management from the eight news related to terrorism as a whole still has in common, which lies in the aspect of single source citation, which only focuses on the Police. From the overall results of bomb news framing analysis in Surabaya, the balance of information has not yet been seen, there is even news that has the same time and occurrence, but the data presented by Detik.Com and Kompas.Com is different